A review on the applications of coal combustion products in China. Issue 5 (26th April 2018) - Li, Jing; Zhuang, Xinguo; Querol, Xavier; Font, Oriol; Moreno, Natalia
ABSTRACT: Owing to the continuous high demand for energy, huge amounts of coals are consumed every year in China, giving rise to large volumes of coal combustion products (CCPs) from coal-fired power plants. Fly ash (FA), bottom ash (BA), boiler slag (BS), and flue gas desulphurization (FGD) gypsum are the primary CCPs generated. The disposal of these CCPs may occupy large areas of useful cultivated land, and cause serious environmental problems. However, these products might be also utilized as recoverable resources. Therefore, it is of economic and environmental significance to carry out research on the utilization of these CCPs. The present review first describes the physicochemical, mineralogical, and environmental geochemical properties of FA, slag, and FGD gypsum. Then the authors focus on the current and potential high value-added applications for these products in China. The utilization of FA for concrete and cement, soil amendment and fertilizer, in the ceramic industry, for catalysis, as adsorbents for the removal of flue gas, heavy metals, dyes and organic compounds, for zeolite and geopolymer synthesis, for recovery of valuable metals, and for recovery of unburned carbon and cenospheres, is discussed. The utilization of slag, such as reclamation of the burnable carbon, use in concrete, cement, and building materials, for roadway pavement and waste-water treatment, and for the production of acoustic barriers is reviewed as well. The current utilization of FGD gypsum includes use as a cement retarder, for the production of building plaster (β-hemihydrated gypsum) and calcium sulphate whiskers (α-hemihydrated gypsum), the production of fire-resistant panels, and use as a fertilizer and soil amendment agent. Furthermore, the possible influence of CCP properties on their utilization, and the advantages and disadvantages of various applications are discussed in this review. Finally, new directions for the future utilization prospects of CCPs in China are proposed.